Payment services in the EU: price regulation to protect a duopoly. Issue 4 (December 2019) - Siragusa, Mario; Dolmans, Maurits; Subiotto, Romano F.; Gilbert, Paul; Messent, John
Abstract : The EU Interchange Fee Regulation ('IFR') introduced price caps on the fees paid between banks in respect of credit and debit card payments. The Second Payment Services Directive ('PSD2') forces some payment schemes to open up their networks to any banks that want to use them. These rules, together with a wealth of related and ancillary provisions, are the legislative fallout from a series of antitrust investigations into Visa and Mastercard. But the rules are not limited to Visa and Mastercard, nor are they limited to schemes that operate in the same way as Visa and Mastercard. They extend to payment schemes with no interchange fees at all and with tiny market shares. One argument made for including all schemes within the scope of the rules was to create a level playing field for competition. Instead, regulation that was initially aimed at Visa and Mastercard has created high entry barriers and hamstrung the only realistic challengers to these four-party schemes. If rival schemes are unable to offer customers or merchants something different, all payment services will become commoditised. Without meaningful rivals, the duopoly of Visa and Mastercard will become more entrenched and customers will see a reduction in choice and innovation. The unintended consequence of the IFR and PSD2 could be to reduce competition in the market, the very thing they were originally designed to address.